Evaluation of genetic purity on Bambara groundnut lines (Vigna subterranean L. Verdcourt) based on qualitative and quantitative characters - Ratria Resti Khoirani; Nurholis Nurholis; Siti Fatimah (Universitas Trunojoyo Madura, 2023)
Evaluation of genetic purity Bambara groundnut hope line is very important to maintain genetic purity before being released into new varieties. The purpose of this research to examine 12 lines of local Bambara groundnuts. The experiment consisted of 12 unit, each containing 30 plants. The data results are analysed of cluster test for variables qualitative, quantitative variables by counting the mean, variance, standard deviation and coefficient of diversity. The results showed that the 7 populations lines of hope were uniform because they had a similarity matrix value above 0.80 and the remaining 5 populations of lines of hope were not uniform because they had a similarity matrix value below 0.80. The results of data analysis on quantitative characters showed that age of germination, flowering, and harvest. Terminal leaf length and width, number of internodes, and number of branches had low diversity. Character number of leaves and, diameter of thecrown at the age of 3, 4, 5, 6, 7 and 10 WAP, petiole length, internode length, weight of wetstover, weight of dry stover, lengt hand width of seeds had moderatediversity. Characters of wetpod weight, pod weightdryness, skin thickness ,number of seeds and seed weight varied from high to very high.